2014
DOI: 10.1590/1415-52732014000300005
|View full text |Cite
|
Sign up to set email alerts
|

Are inappropriate eating behaviors and anxiety related with track and field in adolescent athletes?

Abstract: OBJECTIVE: The study analyzed the relationship between anxiety and inappropriate eating behaviors in adolescent female athletes. METHODS: Eighty-eight track and field athletes aged 12 to 17 years participated in the study. We used the Eating Attitudes Test-26 subscales to assess inappropriate eating behaviors and the Brazilian State - Trait Anxiety Inventory subscales to assess State and Trait anxiety. RESULTS: State - Trait Anxiety Inventory - State (p=0.18) or State - Trait Anxiety Inventory - Trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A study, which was done on women athletes showed the relationship of trait anxiety with oral control and the social and environmental factors that have an effect on food intake. (Fortes, et al, 2014). Mestre et al (2016) showed a positive relationship of trait anxiety and total energy intake from foods in women but not in men.…”
Section: Introductionmentioning
confidence: 89%
“…A study, which was done on women athletes showed the relationship of trait anxiety with oral control and the social and environmental factors that have an effect on food intake. (Fortes, et al, 2014). Mestre et al (2016) showed a positive relationship of trait anxiety and total energy intake from foods in women but not in men.…”
Section: Introductionmentioning
confidence: 89%
“…Several concerns have been identified about health-related issues such as the early specialization of TAF athletes, 63 psychomotor performance, 64 anxiety, inappropriate eating behaviors, 65 doping, 66 access to medical services 67 and psychological aspects. 68 Capranica et al 63 considered the debate if early specialization (ie, engagement in training focusing on a single event such as long jump instead of jumps) would lead to better performance compared to a late specialization.…”
Section: Healthmentioning
confidence: 99%
“…They found that externally paced sport training such as basketball resulted in significantly shorter reaction time compared to self-paced sport such as TAF and sedentary condition. Moreover, Fortes et al 65 analyzed the relationship between anxiety and inappropriate eating behaviors in adolescent female TAF athletes (age 12–17 years). They observed that State – Trait Anxiety Inventory – Trait was associated to oral control and the environmental and social factors that facilitate food consumption in girls.…”
Section: Healthmentioning
confidence: 99%